Birds like it Corky: the influence of habitat features and management of 'montados' in breeding bird communities. - Godinho, Carlos (2012)
In the southwest part of the Iberian Peninsula the dominant land-use are the Portuguese montados and Spanish dehesas, parkland forested areas of anthropogenic origin dominated by cork oak. They form a wooded matrix with open areas, scattered woodlands and undisturbed patches of Mediterranean forest and scrublands. The montados are characterized by a rich bird community. We have focus our study in a multidisciplinary approach, evaluating how management and landscape patterns influence the bird community in order to identify potential threats to its conservation. The study was conducted in the Site of Community Importance of Serra de Monfurado were 70% of the area is cork and holm oaks. We used data from 120 10-min point counts. Using variation partitioning, we determined the independent and joint effects of Forest, Management and Habitat variables. The variation captured in bird assemblage was 65.06%. Most of the explained variation was related to the Habitat and Management variables. The explanatory variables that were highlighted as important predictors were variables that reflected tree and shrub density and cork removal. Modelling for forest species through generalized linear models (GLM) emphasize that the management plays an important role in the species distribution. The most important variables selected in models reflected cattle grazing and cork removal. Our results point out that the type of management is crucial to maintain the equilibrium in bird community associated to montados. Farmland and forest species will benefit from areas with different tree densities, small patches of Mediterranean scrubs in the understory and correct livestock numbers.